Upper limb aerobic training improves aerobic fitness and all-out performance of America's Cup grinders - Adami, P. E.; Delussu, A. S.; Rodio, A.; Squeo, M. R.; Corsi, L.; Quattrini, F. M.; Fattorini, L.; Bernardi, M. (European Journal of Sport Science, 2015)
This research on "America's Cup" grinders investigated the effects of a specific eight-week long-arm cranking ergometer (ACE) training on upper body (UB) aerobic fitness (ventilatory threshold - Tvent, respiratory compensation point- RCP, -oxygen uptake peak - O2peak) and high intensity working capacity. The training consisted of sessions carried out for 20-30 mins, three times per week, at an intensity between the UB-Tvent and UB-RCP, and replaced part of a typical lower limb aerobic training whilst maintaining the usual weekly schedule of callisthenics, resistance training and sailing. Seven sailors, including four grinders and three mastmen (age 30 ± 5.5 years, height 1.9 ± 0.04 m, body mass 102 ± 3.6 kg), were evaluated through both an ACE cardiopulmonary maximal exercise test (CPET) and an ACE all-out up to exhaustion exercise test, before and after the ACE training. UB aerobic fitness improved significantly: UB-O2peak increased from 4.29 ± 0.442 to 4.52 ± 0.522 l·min-1 (6.4 ± 3.66%), O2 at UB-Tvent from 2.42 ± 0.282 to 2.97 ± 0.328 l·min-1 (22.8 ± 5.09%) and O2 at UB-RCP from 3.25 ± 0.402 to 3.75 ± 0.352 l·min-1 (16.1 ± 10.83%). Peak power at the ACE CPET increased from 351 ± 27.5 to 387 ± 33.5 W (10.5 ± 6.93%). The all-out test total mechanical work increased from 28.9 ± 2.35 to 40.1 ± 3.76 kJ (72.1 ± 4.67%). In conclusion, a high intensity aerobic ACE training can be effective in improving grinding performance by increasing UB aerobic fitness and all-out working capacity.